2019
DOI: 10.1108/jarhe-11-2018-0225
|View full text |Cite
|
Sign up to set email alerts
|

Course withdrawal: a comparison of business and engineering students in a private university

Abstract: Purpose The purpose of this paper is to investigate the course withdrawal behavior of business and engineering students in a private university. While previous research has studied such behavior, the literature remains sparse and dated. Design/methodology/approach This study uses a negative binomial model in order to model the total number of course withdrawals for 760 students. The data set includes all courses taken by the students, with a total of 25,160 course outcomes. Findings Among the findings of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…One finding is that out of the 24 male students, seven left the question with no response, while only two of the 20 female students did not respond. This finding that female students are more engaged is supported by findings from other studies in the region that have found that female students are more active on online learning management systems (Mozahem, 2020b) and that they are less likely to give up and withdraw from a course (Mozahem, 2019). Another finding from the study was that the female students who did provide a solution "rarely provided any details or articulation of a relationship," while the male students "provided more details, such as using language to describe the rule" (Ahmad and Greenhalgh-Spencer, 2017: 337).…”
Section: Performancesupporting
confidence: 76%
“…One finding is that out of the 24 male students, seven left the question with no response, while only two of the 20 female students did not respond. This finding that female students are more engaged is supported by findings from other studies in the region that have found that female students are more active on online learning management systems (Mozahem, 2020b) and that they are less likely to give up and withdraw from a course (Mozahem, 2019). Another finding from the study was that the female students who did provide a solution "rarely provided any details or articulation of a relationship," while the male students "provided more details, such as using language to describe the rule" (Ahmad and Greenhalgh-Spencer, 2017: 337).…”
Section: Performancesupporting
confidence: 76%
“…However, our results indicated no statistically significant relation between gender and academic failure. Similarly, Mozahem (2019) also argued that course withdrawal rates among engineering courses and among male students in bachelor level are higher. In the same way, D'Uggento et al ( 2020) also reported that Italian female students were more likely to successfully complete their academic courses.…”
Section: Discussionmentioning
confidence: 99%